An Investigation Into The Translation Of Computer-Related Terminology In A Computer Magazine : With Special Reference To Chip Computer And Communication Magazine [P306.A3 H173 2008 f rb]. - Halimatussa' diah, Halimatussa' diah (2008)
Perkembangan teknologi komunikasi dan informasi (ICT) di Indonesia telah memungkinkan komunikasi serta merta dalam dan luar negara.